1984
DOI: 10.1017/s0033291700019875
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a mental hospital strike on general hospital psychiatric services

Abstract: SynopsisData collected from 6043 psychiatric in-patient records were analysed to assess the impact of a strike at a mental hospital on in-patient services in general hospital psychiatric units in St John's, Newfoundland, Canada. As a whole, during the strike general hospital units showed an increase in the number of involuntary admissions, the number of prior mental hospital admissions of patients, and indications of violent or suicidal behaviour; and a decrease in the occupational status of patients admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Four studies scored well, scoring six or above. 12 , 13 , 14 , 15 Several studies scored relatively low on this scale, with five papers scoring three or less. 16 , 17 , 18 , 19 , 20 The remainder of these studies fell somewhere between, scoring four or five.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies scored well, scoring six or above. 12 , 13 , 14 , 15 Several studies scored relatively low on this scale, with five papers scoring three or less. 16 , 17 , 18 , 19 , 20 The remainder of these studies fell somewhere between, scoring four or five.…”
Section: Resultsmentioning
confidence: 99%
“…In one of the earliest studies Norman and Malla 12 examined the impact of a strike on an in‐patient psychiatric hospital. This strike occurred in February 1977, involved ‘non professional’ workers and lasted 17 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation is in keeping with related studies. In terms of the effects of non-attendance, Norman and Malla (1984) reported that a mental hospital strike led to more suicides and increased admission to a general hospital psychiatric unit. Pryce et al (1983) provided evidence suggesting that a non-directive programme of the kind the present unit used to offer maintained social adequacy and prevented relapse, but did not seem to be associated with clinical impovement.…”
Section: Discussionmentioning
confidence: 99%
“…Case records of all psychiatric admissions to the three general hospital units and the mental hospital in St. John's, over a three-year period (October 1975to October 1978, were examined as part of a larger study (Malla et al 1987;Malla and Norman 1983;Norman and Malla 1984). The admission status was recorded as voluntary or involuntary, as per the criteria described below.…”
Section: The Population Figures Are Based On 1976 Census Figures As Pmentioning
confidence: 99%